An integrated experimental and analytical approach for the analysis of the mechanical interaction between metal porous scaffolds and bone: implications for stress shielding in orthopedic implants - Ramaglia Amadasi, Roberto; Rogati, Giulia; Liverani, Erica; Leardini, Alberto; Caravaggi, Paolo (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionMetal porous structures are becoming a standard design feature of orthopedic implants such as joint endoprostheses. The benefits of the pores are twofold: 1) help improve the cementless primary stabilization of the implant by increasing osteointegration and 2) reduce the overall stiffness of the metal implant thus minimizing stress-shielding. While the mechanical interaction between porous implants and bone has been extensively investigated via complex numerical and finite element models, scarce is the in vitro and in vivo data on the effect of porosity and materials on stress and strain distribution in the implant-bone compound.Materials and methodsAn integrated numerical and experimental approach was used to investigate the effect of material and porosity on the mechanical interaction in compression between porous metal scaffolds and bovine cortical bone. 18 × 18 × 6 mm cuboid samples were cut from fresh-frozen bovine cortical bones. A 9 × 6 × 6 cavity was obtained in each sample to allow insertion of CoCrMo porous and full density scaffolds. Digital Image Correlation analysis tracked bone strain during axial compression of the scaffold-bone samples up to bone failure. The experimental strain data were compared to those from finite element analysis (FEA) of the scaffold-bone compound. The effect of scaffold porosity and material - Ti6Al4V and CoCrMo - on bone strain distribution and reactions forces, with respect to full bone samples, was assessed via FEA and an analytical spring-based model of the bone-scaffold compound.ResultsThe experimental data revealed that the porous scaffold resulted in bone strain closer to that of the intact bone with respect to full density scaffolds. FEA showed that Ti6Al4V scaffolds result in bone strain and reaction forces closer to the those in the intact bone with respect to those in CoCrMo scaffolds. The 1,000 µm pores scaffolds resulted significantly more effective in improving reaction forces with respect to the 500 µm pores scaffolds.ConclusionThe present findings confirm that metal porous scaffolds help promote a more uniform distribution to the bone compared to full density implants. Ti6Al4V scaffolds demonstrated a more favorable mechanical interaction compared to CoCrMo. This integrated approach offers valuable insights into the design of orthopedic implants with optimized mechanical and osseointegration properties.